Novel strategies for capturing health-protective mango phytochemicals in shelf stable food matrices. (March 2015) - Guzman, Ivette; Grace, Mary H.; Yousef, Gad G.; Raskin, Ilya; Lila, Mary Ann
Abstract Cost-effective methods for concentration and stabilization of otherwise perishable mango fruit phytoactives into shelf stable high protein ingredients were developed to combat stunting (malnutrition) in rural Africa. Mango juices complexed with sunflower oil and protein-rich legume flours yielded carotenoid-enriched oils and pelleted polyphenol-enriched flour matrices. Carotenoids from juices were concentrated 9–10 times in the fortified sunflower oil. Protein-rich soy and peanut flours captured 2.2–3.2 mg/g polyphenols from the juices. Alternatively, mango juice was sorbed and co-dried with flours, which stably bound the polyphenols, carotenoids, and natural sugars in soy or peanut protein-rich matrices. The concentration of provitamin A carotenoids was almost doubled and total polyphenols were enriched 4–5 times higher in the matrices compared to fresh pureed juice. Both strategies require minimal instrumentation, are compatible with rural village dietary practices; and capture the benefits of otherwise perishable seasonal resources by complexing healthful proteins together with phytoactive compounds.